How valid are synthetic panel estimates of poverty dynamics? - Nicolas Hérault; Stephen P. Jenkins (University of Essex, Institute for Social and Economic Research (ISER), 2018)
A growing literature uses repeated cross-section surveys to derive "synthetic panel" data estimates of poverty dynamics statistics. It builds on the pioneering study by Dang, Lanjouw, Luoto, and McKenzie (Journal of Development Economics, 2014) providing bounds estimates and the innovative refinement proposed by Dang and Lanjouw (World Bank Policy Research Working Paper 6504, 2013) providing point estimates of the statistics of interest. We provide new evidence about the accuracy of synthetic panel estimates relative to benchmarks based on estimates derived from genuine household panel data, employing high quality data from Australia and Britain, while also examining the sensitivity of results to a number of analytical choices. Overall, we are more agnostic about the validity of the synthetic panel approach applied to these two rich countries than are earlier validity studies in their applications focusing on middle- and low-income countries.
Keywords: I32; D31; C52; 330; synthetic panel; pseudo panel; poverty dynamics; poverty entry; poverty exit; BHPS; HILDA